Metalloantitubercular compounds part 3: synthesis, crystal structure, spectroscopy, electrochemistry and antimycobacterial activity of the copper(II) ciproploxacin (cfH) complex and its phenanthroline adduct - Saha, D. K.; Patitungkho, S.; Padhye, S.; Deobagkar, D. N.; Ozarkar, A.; Bhadbhade, Mohan M.; Gonnade, Rajesh G. (Transition Metal Chemistry, 2005)
The X-ray crystal structures of two ciprofloxacin compounds, viz. [Cu(cfH)(2)(Cl)(2)] (.) 2MeOH (.) 6H2O (2) and [Cu(cfH)(phen)Cl]BF4 (.) 4H(2)O (3) are reported. Complex ( 2) has a distorted octahedral geometry, whereas for the nitrogen adduct (3) a distorted square-pyramidal geometry is seen. Significant enhancement in the antimycobacterial activity of the copper conjugates correlates with their copper redox couples (Cu2+/Cu+) probably due to its relevance to intracellular accumulations and subsequent role in generating oxidative stress.